2021
DOI: 10.1186/s13223-021-00569-8
|View full text |Cite
|
Sign up to set email alerts
|

Pre-existing asthma as a comorbidity does not modify cytokine responses and severity of COVID-19

Abstract: Background A significant portion of COVID-19 sufferers have asthma. The impacts of asthma on COVID-19 progression are still unclear but a modifying effect is plausible as respiratory viruses are acknowledged to be an important trigger for asthma exacerbations and a different, potentially type-2 biased, immune response might occur. In this study, we compared the blood circulating cytokine response to COVID-19 infection in patients with and without asthma. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 29 publications
0
8
0
1
Order By: Relevance
“…Of 83 articles, 77 articles were excluded because 38 articles were duplicated, 7 did not report related data, 18 were review articles, 6 did not stratify TFPI levels according to disease severity or just reported temporal changes of TFPI levels, one was a case report, one was invitro study, one was viewpoint, four studies were without healthy controls, and the results of one study about TFPI value was correlation analysis on the reported data in Al-Tamimi et al [25] work that we had included this data in the analysis, so it was removed. Finally, with the agreement of both reviewers, six articles remained for analysis [25][26][27][28][29][30], as shown in Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of 83 articles, 77 articles were excluded because 38 articles were duplicated, 7 did not report related data, 18 were review articles, 6 did not stratify TFPI levels according to disease severity or just reported temporal changes of TFPI levels, one was a case report, one was invitro study, one was viewpoint, four studies were without healthy controls, and the results of one study about TFPI value was correlation analysis on the reported data in Al-Tamimi et al [25] work that we had included this data in the analysis, so it was removed. Finally, with the agreement of both reviewers, six articles remained for analysis [25][26][27][28][29][30], as shown in Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
“…Three of the six studies were prospective, two were cross-sectional, and one was retrospective with a total of 684 cases and healthy controls, of whom 180 were healthy controls and 504 were COVID-19 patients with different severity (76 mild, 292 moderate, and 136 severe) (Table 1). The severity classification of COVID-19 was defined according to the WHO guidelines in three studies [26,28,29] PRISMA flow diagram demonstrating the data gathering process to finding out coronavirus disease 2019 effect on tissue factor pathway inhibitor levels. Data from [31].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…По данным литературы, частота встречаемости бронхиальной астмы (БА) у больных Covid-19 варьирует в достаточно широком диапазоне -от отсутствия до 9% [4,5,8]. Наличие астмы у больных Covid-19 не было ассоциировано с более частой госпитализацией [9], тяжелым течением, повышенной летальностью [10,11]. Некоторыми авторами показано, что у госпитализированных больных БА уровень сатурации при дыхании комнатным воздухом оставался высоким, кроме того, у них определялись низкие значения С-реактивного белка (СРБ) и ферритина [12].…”
Section: For Citationunclassified